PERSEPSI REMAJA PADA ROMANTISISME FILM DILAN 1990 - Fais, Farida; Sudaryanto, Edy; Andayani, Sri (representamen, 2019)
This study aims to find out how teenagers perceive dilan film romanticism that premieredthroughout Indonesia since January 25, 2018. The method is descriptive method that aims toprovide a picture of a group of people or symptoms. The ongoing research is carried out bythe method of observation, in-depth interviews and documentation as a technique inobtaining data. The perception results shown by adolescents on Sidokapasan X Kec.Simokerto, Surabaya for the Dilan 1990 films are various, and are measured from differentperspectives. The film, titled Dilan 1990, has an influence on adolescents who are stillunstable.Keywords : Perception, Youth, Movie Theaters.